2015
DOI: 10.1115/1.4029777
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Sensitivity of Ignition Delay and Activation Energy in Diesel Combustion

Abstract: The auto-ignition process plays a major role in the combustion, performance, fuel economy, and emission in diesel engines. The auto-ignition quality of different fuels has been rated by its cetane number (CN) determined in the cooperative fuel research engine, according to ASTM D613. More recently, the ignition quality tester (IQT), a constant volume vessel, has been used to determine the derived cetane number (DCN) to avoid the elaborate, time consuming, and costly engine tests, according to ASTM D6890. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…ID 5% is the moment where 5% of fuel chemical energy is released. ID 5% adapts to the change of total energy input when varying injector mass flow (different orifices), injection pressure, injection duration, or fuel components, so that ID 5% is more robust than ID 0.2 in these cases (Joshi et al, 2015;Rabl et al, 2015;Krivopolianskii et al, 2019;Li et al, 2019). ID HTR is determined as the horizontal intercept of the linear fit of the first positive slope of the dHRR/dt profile within the HTR phase.…”
Section: Ignition Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…ID 5% is the moment where 5% of fuel chemical energy is released. ID 5% adapts to the change of total energy input when varying injector mass flow (different orifices), injection pressure, injection duration, or fuel components, so that ID 5% is more robust than ID 0.2 in these cases (Joshi et al, 2015;Rabl et al, 2015;Krivopolianskii et al, 2019;Li et al, 2019). ID HTR is determined as the horizontal intercept of the linear fit of the first positive slope of the dHRR/dt profile within the HTR phase.…”
Section: Ignition Delaymentioning
confidence: 99%
“…Within HTR phase, the change of HRR can be determined using dHRR/dt profile, so that the zero-crossing point of the first positive slope of dHRR/dt, ID HTR , represents a more realistic result for the start of intense high-temperature heat release without using a fixed-value definition. Similar methods such as the ID HRT definition described here were adopted in some studies as well (Joshi et al, 2015;Zhang et al, 2021). Therefore, the ID HTR is employed in this study to characterize the HTR phase while all definitions will be shown while analyzing the results.…”
Section: Ignition Delaymentioning
confidence: 99%
“…(7) is much smaller than the second integral term in Eqn. (7), because the activation energy of natural gas 𝑏 is much higher than the activation energy of the mixture of the fuels 𝑐 [24,32,33]. As such, the exponential term in the second integral is almost 10 9 times as the exponential term in the first integral and the first term can be ignored in the modified knock integral model of dual-fuel engines.…”
Section: Soc Prediction Modelmentioning
confidence: 99%
“…where 𝛼 (π‘˜ + 1), 𝛽 Μ… (π‘˜ + 1), 𝛼 (π‘˜) and 𝛽 Μ… (π‘˜) are the observed parameters at the π‘˜ + 1 cycle and π‘˜ cycle, respectively; πœ‚ indicates the learning rate of the algorithm; and and are the gradients given in Eqns. (33) and (34).…”
Section: Adaptive Controller Designmentioning
confidence: 99%
See 1 more Smart Citation